(untitled) (SAARC Journal of Agriculture, 2017)
The study was attempted to analyze the impact of one house one farm approach on farmers livelihood status in some selected areas of Mymensingh district. As the study was based on comparing the farmers livelihood, a total of 90 farmers where 45 farmers were selected randomly who were under this project and the rest of 45 farmers were selected who were not under this project from Bhabkhali, Char Nilakshmia and Char Ishwardia union under sadar upazila. The primary data were collected through direct interview method from the selected farmers using structured questionnaire. Data were analyzed with a combination of descriptive statistics and econometric analyses like logistic regression and propensity score matching methods to attain the objectives. Sex distribution, family size, training exposure and farm income have positive and significant impact on the adoption of this project. Based on Kernel and Radius matching methods, the average farm household income of the project farmer was increased by the amount of Tk. 28,561.4 to Tk. 16,445.6 per year compared to non-project farmers which is statistically significant at 1% level. Overall employment opportunities were increased by the duration of 22 to 36 man-days for the project farmers compared to non-project farmers. Daily per capita calorie intake from different food items was higher for project farmers than the non-project farmers. The access on human capital, social capital, natural capital, physical capital and financial capital for project farmers were increased by 29.5%, 25.7%, 9.0%, 18.3% and 22.3%, respectively due to the adoption of one house one farm approach. The study also identified some problems faced by the farmers for adopting the project and probable solutions related to those problems. If these problems could be solved within a reasonable time, farmers would be more enthusiastic to adopt the project idea for earning more income which helps them to change their livelihood status ultimately. SAARC J. Agri., 14(2): 90-106 (2016)